Keadilan sebagai Transformasi Kesadaran: Kritik Humanistik–Eksistensial atas Reduksionisme Struktural dalam Diskursus Sosial Kontemporer - Intan Faizatun Nabilah; Khamidatun Nisa’; Revalina Nabillah; Ali Hasan Siswanto (Indo Publishing, 2026)
Contemporary social justice discourse is still dominated by a structural approach that emphasizes resource distribution and institutional regulation, but tends to ignore the inner dimension and human consciousness. This limitation creates a significant research gap, namely the absence of integration between psychological-humanistic approaches, existential dimensions, and theological-spiritual frameworks in understanding and transforming justice. This article aims to reconstruct the concept of justice as a process of consciousness transformation through a synthesis of Abraham Maslow's Humanistic-Existential Psychology with theological and Sufi perspectives. The theoretical approach used is integrative-interdisciplinary, combining the concepts of self-actualization and self-transcendence with the values of justice in Islamic spiritual traditions. This research uses a qualitative-conceptual method with a hermeneutic-critical approach to classical and contemporary literature. The main argument of this article emphasizes that justice is not merely the result of structural engineering, but rather an existential process rooted in the transformation of individual consciousness toward an orientation toward transcendent values. Thus, justice is understood as an ethical-spiritual praxis that moves from the individual to the collective level. The scientific contribution of this research lies in the development of an integrative justice framework model that integrates psychological, structural, and spiritual dimensions as a new basis for transformative justice theory. This model offers a more holistic and relevant alternative perspective for the development of justice studies in the context of contemporary global and Muslim societies.